Comparative assessment of identification indicators of the mineral waters of the Nagutsky and Essentuksky deposits by the example of medical and table waters “Nagutskaya‑4” and “Essentuki no. 4 - E. M. Sevostyanova; M. Yu. Ganin (Пищевые системы)
Currently, Russia occupies a leading position in the world in terms of mineral water reserves and the production of packaged mineral drinking water based on them. Identification of food products is one of the modern problems of mankind, which fully applies to packaged mineral water. The article discusses the relevance of developing methodological approaches to the choice of identification indicators of packaged mineral waters. Packaged mineral waters are not only recognized as a food product, but also are a valuable natural balneotherapeutic resource that has a therapeutic and prophylactic effect on the human body. In this regard, the most important task is to develop scientifically based principles and algorithms for determining the geographical origin and authenticity of packaged mineral waters. Currently, the area of traditionally normed indicators of the quality and safety of mineral waters does not imply the possibility of unambiguous identification of products by geographical, natural, and other characteristics. The purpose of this study was to investigate the physicochemical parameters and isotopic characteristics of the mineral water “Nagutskaya — 4” to develop a set of identification indicators. Water quality and compliance with established standards were assessed by organoleptic (transparency, color, taste and smell) and physicochemical (basic composition, mineralization, biologically active components, microcomponents) parameters. Analytical studies of the isotopic characteristics of water were carried out on a Delta V Advantage isotope mass spectrometer with a GasBench II modular set-top box. A list of indicators for the identification of mineral water “Nagutskaya — 4” is proposed, in which, in addition to the main indicators, it is recommended to include fluorides, toxic metals (lithium, strontium, barium) and biologically active components (iodine and bromine), which are typical for this group of waters. It was from the well of the Nagutskoye deposit that packaged water was sold under the brand name “Essentuki No. 4” in the recent past. Therefore, a comparative assessment of the identification indicators of the mineral medicinal table waters “Nagutskaya‑4” and “Essentuki No. 4” was carried out. The results of the assessment showed statistical differences both in the main identification indicators (basic composition, mineralization, biologically active components) and in additional ones (trace components and isotopic characteristics).